MOESM1 of Is transport distance correlated with animal welfare and carcass quality of reindeer (Rangifer tarandus tarandus)? - Laaksonen, Sauli; Pikka Jokelainen; Pusenius, Jyrki; Oksanen, Antti (Figshare, 2017)
Additional file 1. Meat inspection decision for reindeer slaughter in Finland (translated from Finnish).